45, X product of conception after preimplantation genetic diagnosis and euploid embryo transfer: evidence of a spontaneous conception confirmed by DNA fingerprinting. Issue 1 (December 2016) - Bettio, Daniela; Capalbo, Antonio; Albani, Elena; Rienzi, Laura; Achille, Valentina; Venci, Anna; Ubaldi, Filippo Maria; Levi Setti, Paolo Emanuele
Abstract Background Preimplantation genetic screening (PGS) provides an opportunity to eliminate a potential implantation failure due to aneuploidy in infertile couples. Some studies clearly show that twins following single embryo transfer (SET) can be the result of a concurrent natural conception and an incidence as high as 1 in 5 twins has been reported. In our case PGS was performed on trophectoderm (TE) biopsies by quantitative polymerase chain reaction (qPCR). The product of conception (POC) was cytogenetically investigated after selection of the placental villi by means of the direct method. Molecular cytogenetic characterization of the POC was performed by fluorescence in situ hybridization (FISH) and array-comparative genomic hybridization (a-CGH) analyses. To investigate the possibility of a spontaneous conception, a panel of 40 single nucleotide polymorphisms (SNPs) was used to compare genetic similarity between the DNA of the POC and the DNA leftover of the TE biopsy. Findings We describe a 36-year old infertile woman undergoing PGS who had a spontaneous abortion after a single euploid embryo transfer on a spontaneous cycle. The POC showed a 45, X karyotype confirmed by FISH and a-CGH. DNA fingerprinting demonstrated a genetic similarity of 75 % between the DNA of the POC and TE biopsy, consistent with a sibling status. All supernumerary euploid embryos were also tested showing a non-self relationship with the POC, excluding a mix-up event at the time of fetal embryo transfer. Conclusions DNA fingerprinting of the transferred blastocyst and POC, confirmed the occurrence of a spontaneous conception. This case challenges the assumption that a pregnancy after assisted reproductive technology (ART) is always a result of ART, and strengthens the importance to avoid intercourses during PGS and natural transfer cycles. Moreover, cytogenetic analysis of the POCs is strongly recommended along with fingerprinting children born after PGS to see what the concordance is between the embryo transferred and the resultant child.